Molecular detection of Rickettsia felis in dogs, rodents and cat fleas in Zambia - Moonga, Lavel Chinyama; Hayashida, Kyoko; Nakao, Ryo; Lisulo, Malimba; Kaneko, Chiho; Nakamura, Ichiro; Eshita, Yuki; Mweene, Aaron S.; Namangala, Boniface; Sugimoto, Chihiro; Yamagishi, Junya (Parasites & vectors, 2019)
Flea-borne spotted fever is a zoonosis caused by Rickettsia felis, a Gram-negative obligate intracellular bacterium. The disease has a worldwide distribution including western and eastern sub-Saharan Africa where it is associated with febrile illness in humans. However, epidemiology and the public health risks it poses remain neglected especially in developing countries including Zambia. While Ctenocephalides felis (cat fleas) has been suggested to be the main vector, other arthropods including mosquitoes have been implicated in transmission and maintenance of the pathogen; however, their role in the epidemiological cycle remains to be elucidated. Thus, the aim of this study was to detect and characterize R. felis from animal hosts and blood-sucking arthropod vectors in Zambia. Dog blood and rodent tissue samples as well as cat fleas and mosquitoes were collected from various areas in Zambia. DNA was extracted and screened by polymerase chain reaction (PCR) targeting genus Rickettsia and amplicons subjected to sequence analysis. Positive samples were further subjected to R. felis-specific real-time quantitative polymerase chain reactions. Rickettsia felis was detected in 4.7% (7/150) of dog blood samples and in 11.3% (12/106) of rodent tissue samples tested by PCR; this species was also detected in 3.7% (2/53) of cat fleas infesting dogs, co-infected with Rickettsia asembonensis. Furthermore, 37.7% (20/53) of cat flea samples tested positive for R. asembonensis, a member of spotted fever group rickettsiae of unknown pathogenicity. All the mosquitoes tested (n = 190 pools) were negative for Rickettsia spp. These observations suggest that R. felis is circulating among domestic dogs and cat fleas as well as rodents in Zambia, posing a potential public health risk to humans. This is because R. felis, a known human pathogen is present in hosts and vectors sharing habitat with humans.